From 3D to 4D printing: a reactor for photochemical experiments using hybrid polyurethane acrylates for vat-based polymerization and surface functionalization. Issue 96 (19th November 2020) - Hansen, Anne; Renner, Melissa; Griesbeck, Axel G.; Büsgen, Thomas
Abstract : A solvent-, air-, and UV-stable isocyanate-functionalized polyacrylate reactor with flow-meter geometry was post-functionalized with porphyrin and benzophenone catalysts and applied for photoinitiated energy- and hydrogen-transfer catalysis. Abstract : The vat-based 3D printing of a chemical reactor with flow-meter geometry from an isocyanate-functionalized acrylate monomer followed by post-processing with amino-functionalized photocatalysts is described. This approach results in solvent- and air-stable flow photochemical reactors with UV-A transparent windows that can be applied for photooxygenation and photo redox catalysis.